2015
DOI: 10.1093/rheumatology/kev306
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression and anxiety predict treatment response and long-term physical health outcomes in rheumatoid arthritis: secondary analysis of a randomized controlled trial

Abstract: Objective. The aim of this analysis is to examine the longitudinal impact of symptoms of depression/anxiety on treatment response, long-term disease activity and physical disability in RA.Methods. Secondary analysis of clinical trial data was performed. Data were collected at baseline and at 6-monthly intervals for 2 years. The EuroQoL (EQ-5DTM) indicated depression/anxiety symptom severity. Our primary outcomes of interest were (i) DAS-28 and (ii) physical disability measured via the HAQ. Secondary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
120
2
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 31 publications
14
120
2
15
Order By: Relevance
“…В недавней работе 2016 г. F. Matcham и соавт. [7] сделали те же выводы, а также показали, что депрессия снижает ответ на ГК у больных РА. Проведенное нами исследование также демонстрирует, что персистирую-щие ПР при отсутствии ПФТ способствуют менее зна-чимому снижению индексов воспалительной активно-сти РА, преимущественно за счет ЧБС и ООСЗ, а также уменьшают эффективность БПВП и ГИБП, которая оценивалась по критериям EULAR и динамике индекса SDAI.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…В недавней работе 2016 г. F. Matcham и соавт. [7] сделали те же выводы, а также показали, что депрессия снижает ответ на ГК у больных РА. Проведенное нами исследование также демонстрирует, что персистирую-щие ПР при отсутствии ПФТ способствуют менее зна-чимому снижению индексов воспалительной активно-сти РА, преимущественно за счет ЧБС и ООСЗ, а также уменьшают эффективность БПВП и ГИБП, которая оценивалась по критериям EULAR и динамике индекса SDAI.…”
Section: Discussionunclassified
“…К их числу от-носят женский пол, пожилой возраст, избыточную массу тела, курение, ряд молекулярных биомаркеров, антитела к применяемому ГИБП и некоторые другие [4]. Инте-ресно, что сопутствующие РА расстройства тревожно-депрессивного спектра (РТДС) и когнитивные наруше-ния (КН) в последние годы также рассматривают в каче-стве предикторов недостаточного ответа на терапию БПВП и ГИБП [5][6][7]. Как отмечено в систематическом обзоре A.M. Rathbun и соавт.…”
unclassified
See 1 more Smart Citation
“…Several previous studies have investigated the effects of psychosocial factors on DAS at subsequent visits. In a secondary analysis of a clinical trial in early RA, Matcham et al (12) found that both baseline and persistent symptoms of depression/anxiety symptoms, measured on a combined scale of the EuroQol 5 Dimensions (EQ-5D), were associated with increased DAS28 scores over the first 2 years of follow-up. This is partly in agreement with our study, in which we found both baseline anxiety and depression scores to be associated with higher DAS at 3 months of follow-up, but not at later time-points (12).…”
Section: Discussionmentioning
confidence: 99%
“…Recent interest has been directed towards the influence of psychosocial factors. Several studies have reported significant associations between baseline levels of anxiety and/or depression and subsequent DAS or DAS components (10)(11)(12). However, the effects of psychosocial factors after treatment has been initiated on disease activity have not been extensively studied.…”
mentioning
confidence: 99%